Afetos de um mundo secreto: fabulações de uma formação docente - Barin, Ana Cláudia (2015)
This master s thesis experimented the fabulation to think encounters regarding teachers formation. Such encounters were produced by affects (SPINOZA, 2013) triggered by the animation Coraline (2009). The encounters dialogue with visual diaries were constructed during the Supervised Teaching Practice in the Visual Arts Teaching Major. The memory that I have fabricated was not the one about a recall or a review of what the teaching formation diaries contained, but it was the creation, which might have come from these registers. Moved by Deleuze s (1997) and Deleuze e Guattari s (1995) thoughts, I have produced, with connections from the past, something in constant development, an anti-narrative, about to happen, breaking the time sequences of events. The secret world constructed in this research is not about another world, but this world, here and now, what happens in complete immanence, all that might become. I operated with concepts such as affects and encounters to trace the sewing of this research, to map this rhizome, where methodic thinking is defeated by disorder towards the creation of new territories. The experimentation through the memory was the fabulation, which invades the character Coraline s quotidian and elements present in the pedagogical diaries. The text was built in the mix of such borders, in the teaching living based on the fabulation I produced in this research.